The behavior of tooth brushing with miswak extract toothpaste using a roll technique on the gingival health status of teenagers aged 13-15 years - Panggabean, Welen Yunela (Poltekkes Kemenkes Yogyakarta, 2020)
Behavior is one of the factors causing dental and oral health problems which is influenced by lack of knowledge. Teenagers aged 13-15 years is a critical age of periodontal disease. Riskesdas data (2018) shows the prevalence of dental and oral health problems 57.6% which often occur to teenagers, namely gingivitis. Siwak natural ingredients, contain antibacterial as an alternative treatment for gingivitis. This research aims to determine the effect of tooth brushing behavior with miswak extract toothpaste using a roll technique on the gingival health status of teenagers aged 13-15 years. Method: quasi experimental design one group pretest and posttest design. Sample: 18 adolescents aged 13-15 years. The research path of respondents were given a tooth brushing behavior questionnaire, examination of gingival health status using the gingival index. Data analysis: Paired Sample T-Test test. Results: before the treatment of tooth brushing with miswak extract toothpaste using a roll technique, there are 10 respondents (55.6%) in the sufficient category and there are 14 respondents (77.7%) with moderate health status of gingiva, after the treatment: there are 9 respondents (50%) in the good category of tooth brushing behavior and 11 respondents (61.1%) with mild gingival health status. The results of Paired Sample T-Test of tooth brushing behavior p-value 0,000 (<0.05), gingival health status p-value 0,000 (<0.05). Conclusion: there is an influence of tooth brushing behavior with miswak extract toothpaste using roll technique on the gingival health status of teenagers aged 13-15 years.